Book review. (1st June 2017) - Kingston, William
Abstract : This report, funded by UK Engineering and Physical Sciences Research Council and the International Public Policy Institute, has the great merit of being a study of innovation failure, rather than success, and the number of useful lessons it contains is consequently all the greater. From a massive database, it estimates that, between 2000 and 2017, the UK provided close to half a billion pounds of public sector funding to encourage the private sector to try to capture offshore wave energy. Investment by firms must have been even more. There was nothing tangible to show for all this in the end, primarily because of inadequacies 'in government and industrial strategy to support wave energy innovation in the UK, most notably a premature emphasis on commercialisation and a lack of knowledge exchange.' Public funding only partially covered R&D costs, so that developers tried to reach the stage where their equipment could actually produce saleable energy, without enough testing for faults. This attempt to 'go too far too quickly' was compounded by government's investing heavily in test facilities without providing support for developers to use them. Also, reliance on patent protection caused developers to avoid sharing their information. The public sector did learn some lessons. Wave Energy Scotland was established to carry on the work in a much more modest way, but able to offer 100% funding and to insist that research results were shared among developers. In addition, the European Community introduced the Marinet initiative to fund access by developers to test facilities.